1997
DOI: 10.1007/s004010050665
|View full text |Cite
|
Sign up to set email alerts
|

Cell cycle markers in the hippocampus in Alzheimer's disease

Abstract: Using immunohistochemistry we have analysed the nuclear expression of cyclins A, B, D, and E in neurones in the hippocampi of control subjects and patients suffering from various neurodegenerative disorders including. Alzheimer's disease (AD). Cyclins A and D could not be detected but varying degrees of cyclin E expression were found in all patient groups including control subjects. Cyclin B expression was not detected in control subjects but it was expressed in the subiculum, dentate gyrus and CA1 region in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
200
0
2

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 301 publications
(210 citation statements)
references
References 30 publications
8
200
0
2
Order By: Relevance
“…The next step is the incorporation of a biotin tag to 3AT. Several biotin tags have been shown to be effective such as NHS-biotin (4), sulfo-NHS-SS-biotin (282,286,332), or biotin (199). The enrichment of the biotin-tagged peptides then occurs using an avidin (4) or a streptavidin (286) 1624 BUTTERFIELD ET AL.…”
Section: Fig 10 Outline Of Redox Proteomics Approachmentioning
confidence: 99%
“…The next step is the incorporation of a biotin tag to 3AT. Several biotin tags have been shown to be effective such as NHS-biotin (4), sulfo-NHS-SS-biotin (282,286,332), or biotin (199). The enrichment of the biotin-tagged peptides then occurs using an avidin (4) or a streptavidin (286) 1624 BUTTERFIELD ET AL.…”
Section: Fig 10 Outline Of Redox Proteomics Approachmentioning
confidence: 99%
“…Replicative DNA synthesis in terminally differentiated neurons followed by failures of cell cycle completion is the main principle of cycle theory of Alzheimer’s disease (AD) [50, 51]. Vulnerable neurons of the AD brain exhibit biomarkers of cell cycle progression and DNA replication suggesting a re-entry into the cell cycle [52, 53]. A number of laboratories have reported the re-expression of various cell cycle proteins in neurons from patients with AD: cyclins A [52], B [52], D [53], and E [52], as well as CDKs [51], Proliferating Cell Nuclear Antigen (PCNA) [51, 52], Ki67 [52] and cyclin-dependent kinase inhibitors (CKIs) of both the Ink (Inhibitors of Kinases) and Cip/Kip (CDK interacting protein/Kinase inhibitory protein) families [54, 55].…”
Section: The Podocyte’s Catastrophe: Lost Cell Cycle Controlmentioning
confidence: 99%
“…Vulnerable neurons of the AD brain exhibit biomarkers of cell cycle progression and DNA replication suggesting a re-entry into the cell cycle [52, 53]. A number of laboratories have reported the re-expression of various cell cycle proteins in neurons from patients with AD: cyclins A [52], B [52], D [53], and E [52], as well as CDKs [51], Proliferating Cell Nuclear Antigen (PCNA) [51, 52], Ki67 [52] and cyclin-dependent kinase inhibitors (CKIs) of both the Ink (Inhibitors of Kinases) and Cip/Kip (CDK interacting protein/Kinase inhibitory protein) families [54, 55]. One study demonstrated increased levels of phosphorylated H3 (Ser 10), a key regulator in chromatin compaction during cell division, in neuronal cytoplasm in AD compared to controls, further supporting the hypothesis that neurons in AD are mitotically activated [56].…”
Section: The Podocyte’s Catastrophe: Lost Cell Cycle Controlmentioning
confidence: 99%
“…Despite intensive effort, the pathogenesis of neuronal injury in AD is not completely understood. However, recent studies demonstrate that, in AD, a number of cell cycle elements are up-regulated in the susceptible neurones despite their terminally differentiated status (Masliah et al ., 1993;Smith & Lippa, 1995;Kondratick & Vandre, 1996;Li et al ., 1997;McShea et al ., 1997;Nagy et al ., 1997;Vincent et al ., 1997;Arendt et al ., 1998;Busser et al ., 1998;Illenberger et al ., 1998;Pei et al ., 1998;McShea et al ., 1999;Raina et al ., 2000;Zhu et al ., 2001;Ogawa et al ., 2003). Although the precise mechanism and significance of increased cell cycle elements in diseased neurones remains unclear, it has been suggested that cell cycle elements play a crucial role in neuronal death.…”
Section: Introductionmentioning
confidence: 99%